2021
DOI: 10.3991/ijet.v16i09.19697
|View full text |Cite
|
Sign up to set email alerts
|

Universal Models and Platforms in E-Learning

Abstract: The study describes the effectiveness of digital technological solutions in education. Students, postgraduates, teachers, and medical business representatives have tested a comprehensive educational product based on the capabilities of learning management system (LMS) platforms. The online course was implemented on the e-learning platforms such as Moodle, Schoology, TalentLMS, Canvas LMS, Docebo, iSpringLearn's, Brightspace, Absorb LMS. The implementation of advanced e-learning models ensured the effectivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…Creative communication facilitates the exchange of knowledge, thoughts, and ideas to meet the participants’ educational need for self-expression and creativity (Shurygin et al, 2021 ), and increases communication opportunities through technology, which can impact the socialisation of students with intellectual disabilities. In the words of Tatianchykova et al ( 2020 ), the socialisation of these students requires further technological involvement.…”
Section: Introductionmentioning
confidence: 99%
“…Creative communication facilitates the exchange of knowledge, thoughts, and ideas to meet the participants’ educational need for self-expression and creativity (Shurygin et al, 2021 ), and increases communication opportunities through technology, which can impact the socialisation of students with intellectual disabilities. In the words of Tatianchykova et al ( 2020 ), the socialisation of these students requires further technological involvement.…”
Section: Introductionmentioning
confidence: 99%
“…A study in the USA showed that social media had become one of the models in learning integrated with the name of social media learning activities (SMLA) (Zgheib & Dabbagh, 2020). Viktor Shurygin, in his research, identified various universal platforms in e-learning (Shurygin et al, 2021). So varied the implementation of online learning, even the use of the term alone makes it difficult to distinguish between distance learning, e-learning, and online learning (Moore et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…An online social platform Telegram played a significant role and helpful contribution to language teaching as it did not require fast-paced internet and was very user-friendly both for students and teachers in most parts of the world [20]. However, it was very difficult to give feedback to the student as work submission was not properly organized and students could not get positive washback from the assignment as well as task [19].…”
Section: Introductionmentioning
confidence: 99%
“…According to [19], the digital transformation has generated a new "eco-system of learning", which is called e-learning. E-leaning is defined as the implementation of virtual learning platforms containing instructional materials and a student-centered environment.…”
Section: Introductionmentioning
confidence: 99%